Comparison of the Walad Concept in Islamic Heritage According to the Theory of Hudud Syahrur and Scholars of the Fiqh Mazhab - Jamaluddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research raises the concept of walad and the division of its rights in Islamic heritage according to the theory of Syahrur's hudud and the scholars of the fiqh school of thought. Syahrur does not differentiate the meaning of the word walad in Surah an-Nisa’ verses 11 and 12 and 176. Syahrur interpreted the word walad in Surah an-Nisa’ as a boy and a girl. This opinion is clearly different from the opinion that has developed among Sunni sect scholars. Scholars of the school of thought interpret the word walad in Surah an-Nisa’ verse 176 as a boy. This opinion has 2 reasons. First they use the pronunciation of walad isti'mali. Arabs interpret the pronunciation of walad as just a boy in letters (a daily habit), the second pronunciation of walad is interpreted in hamlu because there are three hadiths as supports. These three hadiths say that girls cannot spend their wealth. Syahrur established three forms of legal boundaries in the distribution of inheritance for boys and girls. The first is the maximum share limit for boys 66.6% and the minimum share limit for girls 33.3%. The second is the minimum limit that girls must receive 2/3. The third is that the minimum limit for girls gets half (50%) of the property share. Meanwhile, according to school scholars, the share received by a boy is the same as two parts for a girl. This understanding is interpreted through a bayani approach.